A thermoplastic building template and its manufacturing method
By adopting thermoplastic building formwork, using a combined structure of core material and skin, and through the composite pressing process of a double steel belt continuous press, the existing building formwork has been solved, and the effects of lightweight, high strength, easy mold release and environmental protection are achieved.
Patent Information
- Application Number
- CN202510131825.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-04-04
AI Technical Summary
The existing building formwork has problems such as heavy weight, high cost, difficulty in processing, impatient aging and demolding in use, and it is difficult to meet the construction industry's needs for high quality, low cost and environmental protection.
Thermoplastic building formwork, including core material, skin and PP sheet film arranged symmetrically outward, are used to composite press through a double steel belt continuous press to create a lightweight and high-strength building formwork.
The overall lightweight and high strength of the building formwork is achieved, and the static curve strength, static curve modulus, drum peel strength, compression strength and shear strength are improved. After the 1000h anti-aging and anti-oxidation test, the surface and core material have no powdering and yellowing, making it easy to release mold.
Smart Images

Figure CN119749023A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of construction, in particular to a thermoplastic construction template and a manufacturing method thereof. Background Art
[0002] Building formwork is a temporary support structure, which is made according to the design requirements to shape the concrete structure and components according to the specified position and geometric size, maintain its correct position, and bear the deadweight of the building formwork and the external loads acting on it. The building formwork plays a supporting and positioning role in the concrete pouring process, ensuring that the concrete can form the expected shape and size during the curing process. At the same time, it can also improve construction efficiency, reduce project costs, and ensure the quality and safety of concrete projects.
[0003] At present, there are mainly the following categories of building formwork: 1. Wooden building formwork. Wooden building formwork usually consumes a large amount of wood, is not wear-resistant, has low bending strength, is not easy to demold during use, has a small number of recycling times, and is not resistant to aging; 2. Steel building formwork. Although steel building formwork is easy to construct and has strong versatility, it is heavy, expensive, and difficult to process; 3. Aluminum building formwork. Aluminum building formwork is heavy, expensive, easy to deform, difficult to demold, and not resistant to aging.
[0004] Therefore, how to ensure high quality, low cost and environmental protection in the construction industry is one of the key issues that people are thinking about.
[0005] The patent application with publication number CN105604312A discloses a fiber-reinforced building formwork and a preparation method thereof, comprising a board core and a surface layer covering the upper and lower surfaces of the board core, wherein the board core comprises a plurality of layers of wood veneer with wood fibers bonded together, and the wood fibers of adjacent wood veneers are perpendicular to each other, and the surface layer comprises 1 to 4 layers of fiber-reinforced prepreg sheets compositely connected together, wherein the fiber-reinforced prepreg sheets are composited from fiber products and polymer resins. This type of formwork has excellent mechanical properties, good waterproof and anti-damage properties, and a long service life, which reduces the single-use cost of the formwork, and is more environmentally friendly because it avoids the use of wood. However, the weight of the building formwork is heavy and the preparation process is relatively complicated. . Summary of the invention
[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a thermoplastic building formwork with high strength, low weight, easy demoulding, high recycling times and aging resistance and a manufacturing method thereof.
[0007] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:
[0008] A thermoplastic building template comprises a core material, a skin and a first PP film which are symmetrically arranged on both sides of the core material outward in sequence, wherein the first PP film is bonded to the skin through a first adhesive film, and the skin is bonded to the core material through a second adhesive film.
[0009] Preferably, the core material is a PP honeycomb core with a wall thickness of 0.20-0.50 mm, a tube diameter of 5.0-15.0 mm, and a density of 100-300 kg / m 3 .
[0010] Preferably, the skin comprises, from outside to inside, a second PP sheet film, a first longitudinal unidirectional tape, a prepreg and a second longitudinal unidirectional tape, wherein the first longitudinal unidirectional tape and the second longitudinal unidirectional tape are both continuous glass fiber reinforced PP unidirectional tapes, the glass fiber content of the continuous glass fiber reinforced PP unidirectional tape is 50% to 70%, and the first longitudinal unidirectional tape and the second longitudinal unidirectional tape are both 0.4-0.8mm; the thickness of the skin is 1.0-2.0mm.
[0011] Preferably, the prepreg is a PP-based glass fiber prepreg, the PP content in the prepreg is 50% to 70%, and the thickness of the prepreg is 0.3-0.6 mm.
[0012] Preferably, the PP bending strength in the first longitudinal unidirectional tape and the second longitudinal unidirectional tape is ≥300 MPa.
[0013] Preferably, the second adhesive film is a PP hot melt adhesive film, and the weight of the second adhesive film is 50-200 g / m 2 , melting point is 90-180℃.
[0014] Preferably, the first PP film sheet and the second PP film sheet both include a PP film and a spunlace nonwoven fabric, wherein the PP film in the first PP film sheet is arranged toward a side away from the core material; and the thickness of the first PP film sheet and the second PP film sheet are both 0.1-0.3 mm.
[0015] Preferably, the first adhesive film is a PP hot melt adhesive film, and the weight of the first adhesive film is 50-200 g / m 2 , melting point is 90-180℃.
[0016] Preferably, 0.01%-6% of anti-aging agent is added to the first PP film, the first adhesive film, the skin, the second adhesive film and the core material.
[0017] A method for manufacturing the thermoplastic building formwork as described above comprises the following manufacturing steps:
[0018] Step 1: Lay a first PP sheet film, a first adhesive film, a skin and a second adhesive film in sequence on a double steel belt continuous press to form a dough skin, wherein the hot plate temperature of the double steel belt continuous press is 180-250°C and the pressure is 0.5kg / m2 -10kg / m 2 The vehicle speed is between 0.5-5.0m / min;
[0019] Step 2: Lay the dough prepared in step 1 on the upper and lower sides of the core material, and put it into a double steel belt continuous press to composite and press it into a thermoplastic building formwork, wherein the hot plate temperature of the double steel belt continuous press is 180-250°C and the pressure is 0.5kg / m 2 -10kg / m 2 The vehicle speed is between 0.5-5.0m / min.
[0020] The present invention has the following beneficial effects due to the adoption of the above technical scheme: the present invention discloses a thermoplastic building template and a manufacturing method thereof, wherein the thermoplastic building template comprises a core material and a skin and a first PP sheet film which are sequentially and symmetrically arranged on both sides of the core material outward, and the thermoplastic building template is obtained by secondary composite manufacturing by using a double steel belt continuous press. The thermoplastic building template is light and high in strength as a whole, and has high static bending strength, static bending modulus, roller peeling strength, compression strength and shear strength. After a 1000-hour anti-aging and anti-oxidation test, the surface and the core material of the thermoplastic building template have no powdering and yellowing phenomenon, and the surface is smooth and flat without pits and convex points, so it is easy to demould. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the structure of the present invention;
[0022] Figure 2 It is a schematic diagram of the structure of the skin in the present invention.
[0023] Reference numerals:
[0024] 1. First PP film; 2. First adhesive film; 3. Skin; 31. Second PP film; 32. First longitudinal unidirectional tape; 33. Prepreg; 34. Second longitudinal unidirectional tape; 4. Second adhesive film; 5. Core material. DETAILED DESCRIPTION
[0025] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0026] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0027] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more, unless otherwise clearly specified.
[0028] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly below and obliquely below the second feature, or simply indicates that the first feature is lower in level than the second feature.
[0029] like Figure 1 As shown, the present invention discloses a thermoplastic building formwork, comprising a core material 5 and a skin 3 and a first PP film 1 symmetrically arranged on both sides of the core material 5 outward in sequence, the first PP film 1 being bonded to the skin 3 via a first adhesive film 2, and the skin 3 being bonded to the core material 5 via a second adhesive film 4.
[0030] In the present invention, the core material 5 is a PP honeycomb core, which is made by extruding a round tube through a twin-screw extruder. The wall thickness of the core material 5 is 0.20-0.50 mm, the tube diameter is 5.0-15.0 mm, and the density is 100-300 kg / m 3 In order to ensure the anti-oxidation and anti-aging effects, 0.01%-6% of anti-aging agent needs to be added to the core material 5 .
[0031] like Figure 2As shown, the skin 3 includes a second PP sheet film 31, a first longitudinal unidirectional tape 32, a prepreg 33 and a second longitudinal unidirectional tape 34 from the outside to the inside. The thickness of the skin 3 is 1.0-2.0 mm. The skin 3 is compounded by a double steel belt continuous press. In order to ensure the anti-oxidation and anti-aging effects, 0.01%-6% of anti-aging agent is added to the skin 3.
[0032] Among them, the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 are both continuous glass fiber reinforced PP unidirectional tapes, the glass fiber content in the continuous glass fiber reinforced PP unidirectional tape is 50% to 70%, and the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 are both 0.4-0.8 mm. Since the building formwork bears greater force in the longitudinal direction during use, the use of longitudinal unidirectional tapes can provide higher bending strength and high bending strength at a lower cost. The bending strength of PP in the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 is ≥300 MPa.
[0033] The prepreg 33 is a PP-based glass fiber prepreg. The PP-based glass fiber prepreg is made of PP and glass fiber by low-pressure impregnation. Due to its special surface texture, the surface of the thermoplastic building formwork can be made with fewer bubbles and pores. The thickness of the prepreg 33 is 0.3-0.6mm. The second adhesive film 4 is a PP hot-melt adhesive film. The PP content in the prepreg 33 is 50% to 70%. Due to the high PP content, the core material 5 can be better bonded to the skin 3 through the second adhesive film 4, thereby improving the overall strength of the thermoplastic building formwork while providing stronger bonding force. In the present invention, the gram weight of the second adhesive film 4 is 50-200g / m 2 , the melting point is 90-180°C. In order to ensure the anti-oxidation and anti-aging effects, 0.01%-6% of anti-aging agent is added to the second adhesive film 4.
[0034] The first PP film 1 and the second PP film 31 both include a PP film and a spunlace non-woven fabric, which are compounded by a double steel belt continuous press, and the temperature during production needs to be 160-180°C to ensure that the PP film can be completely infiltrated into the spunlace non-woven fabric, wherein the PP film in the first PP film 1 is arranged toward the side away from the core material 5, thereby ensuring that the thermoplastic building material has a smooth appearance, no pits and is easy to demold, and in order to ensure anti-oxidation and anti-aging effects, 1%-3% of an anti-aging agent is added to the first PP film 1; the thickness of the first PP film 1 and the second PP film 31 are both 0.1-0.3mm.
[0035] The first adhesive film 2 is a PP hot melt adhesive film, and the weight of the first adhesive film 2 is 50-200g / m 2 , the melting point is 90-180°C. In order to ensure the anti-oxidation and anti-aging effects, 0.01%-6% of anti-aging agent is added to the first adhesive film 2.
[0036] Antioxidants are usually organic compounds containing sulfur, nitrogen or phosphorus, which can be granulated by a single-screw extruder and mixed into the PP materials of the core material 5, the skin 3, the first PP sheet film 1, the first film 2 and the second film 4 to achieve anti-aging and anti-oxidation effects.
[0037] The present invention also discloses a method for manufacturing the thermoplastic building template as described above, comprising the following manufacturing steps:
[0038] Step 1: Lay a first PP sheet film 1, a first adhesive film 2, a skin 3 and a second adhesive film 4 in sequence on a double steel belt continuous press to form a dough skin, wherein the hot plate temperature of the double steel belt continuous press is 180-250°C and the pressure is 0.5kg / m 2 -10kg / m 2 The vehicle speed is between 0.5-5.0m / min;
[0039] Step 2: Lay the dough prepared in step 1 on the upper and lower sides of the core material 5, and put it into a double steel belt continuous press to composite and press it into a thermoplastic building template, wherein the hot plate temperature of the double steel belt continuous press is 180-250°C and the pressure is 0.5kg / m 2 -10kg / m 2 The vehicle speed is between 0.5-5.0m / min.
[0040] The prepared building formwork was tested according to the following standards:
[0041] Static flexural strength and static flexural modulus: GB / T 17657-2013 Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels;
[0042] Roller peel strength: GB / T 1457-2005 Sandwich structure roller peel strength test method;
[0043] Compression strength: GB / T 1453-2005 Test method for flat compression performance of sandwich structures or cores;
[0044] Shear strength: GBT 1455-2005 Sandwich structure or core shear performance test method;
[0045] Weathering Tests: SAE J2020: Accelerated Exposure of Automotive Exterior Materials Using Fluorescent UV and Condensation Devices.
[0046] The test results must meet customer requirements as follows: static flexural strength > 100MPa, static flexural modulus > 9500MPa, roller peel strength 250N·mm / mm, compression strength > 9.0MPa, shear strength > 2.4MPa, after 1000h anti-aging and anti-oxidation test, the surface PP film has no powdering or yellowing, and the core material has no powdering or yellowing.
[0047] Embodiment 1:
[0048] A method for manufacturing a thermoplastic building template comprises the following manufacturing steps:
[0049] Step 1: Lay a first PP film 1, a first adhesive film 2, a skin 3 and a second adhesive film 4 in sequence on a double steel belt continuous press to form a dough skin, wherein the hot plate temperature of the double steel belt continuous press is 250°C and the pressure is 0.5kg / m 2 , speed 5.0m / min;
[0050] Step 2: Lay the dough prepared in step 1 on the upper and lower sides of the core material 5, and put it into a double steel belt continuous press to composite and press it into a thermoplastic building formwork sample, wherein the hot plate temperature of the double steel belt continuous press is 250°C and the pressure is 0.5kg / m 2 , vehicle speed 5.0m / min.
[0051] The first PP film 1 is 0.1 mm, the PP bending strength in the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 in the skin 3 is 320 MPa, the thickness of the skin 3 is 1.0 mm, the core material 5 is a PP honeycomb core, and the density of the core material 5 is 300 kg / m 3 Anti-aging agents are added to the core material 5, the skin 3, the first PP film 1, the first adhesive film 2 and the second adhesive film 4.
[0052] The performance tests were carried out on the thermoplastic building formwork samples, and the test results were as follows: static flexural strength 125MPa, static flexural modulus 11500MPa, roller peel strength 265N·mm / mm, compression strength 11MPa, shear strength 2.63MPa, anti-aging and anti-oxidation effects: after 1000h anti-aging and anti-oxidation test, the first PP film 1 had no powdering and yellowing phenomenon, and the core material 5 had no powdering and yellowing phenomenon; Surface effect: The surface is smooth and flat without pits or convex spots.
[0053] Embodiment 2:
[0054] A method for manufacturing a thermoplastic building template comprises the following manufacturing steps:
[0055] Step 1: Lay a first PP sheet film 1, a first adhesive film 2, a skin 3 and a second adhesive film 4 in sequence on a double steel belt continuous press to form a dough skin, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m 2 , speed 3.0m / min;
[0056] Step 2: Lay the dough prepared in step 1 on the upper and lower sides of the core material 5, and put it into a double steel belt continuous press to composite and press it into a thermoplastic building formwork sample, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m2 , vehicle speed 3.0m / min.
[0057] The first PP film 1 is 0.2 mm, the PP bending strength of the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 in the skin 3 is 320 MPa, the thickness of the skin 3 is 2.0 mm, the core material 5 is a PP honeycomb core, and the density of the core material 5 is 200 kg / m 3 Anti-aging agents are added to the core material 5, the skin 3, the first PP film 1, the first adhesive film 2 and the second adhesive film 4.
[0058] The performance tests were carried out on the thermoplastic building formwork samples, and the test results were as follows: static flexural strength 110MPa, static flexural modulus 10200MPa, roller peel strength 258N·mm / mm, compression strength 9.5MPa, shear strength 2.45MPa, anti-aging and anti-oxidation effects: after 1000h anti-aging and anti-oxidation test, the first PP film 1 had no powdering and yellowing phenomenon, and the core material 5 had no powdering and yellowing phenomenon; Surface effect: The surface is smooth and flat without pits or convex spots.
[0059] Embodiment 3:
[0060] A method for manufacturing a thermoplastic building template comprises the following manufacturing steps:
[0061] Step 1: Lay a first PP film 1, a first adhesive film 2, a skin 3 and a second adhesive film 4 in sequence on a double steel belt continuous press to form a dough skin, wherein the hot plate temperature of the double steel belt continuous press is 180°C and the pressure is 10kg / m 2 , speed 0.5m / min;
[0062] Step 2: Lay the dough prepared in step 1 on the upper and lower sides of the core material 5, and put it into a double steel belt continuous press to composite and press it into a thermoplastic building formwork sample, wherein the hot plate temperature of the double steel belt continuous press is 180°C and the pressure is 10kg / m 2 , vehicle speed 0.5m / min.
[0063] The first PP film 1 is 0.3 mm, the PP bending strength in the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 in the skin 3 is 320 MPa, the thickness of the skin 3 is 2.0 mm, the core material 5 is a PP honeycomb core, and the density of the core material 5 is 200 kg / m 3 Anti-aging agents are added to the core material 5, the skin 3, the first PP film 1, the first adhesive film 2 and the second adhesive film 4.
[0064] The performance tests were carried out on the thermoplastic building formwork samples, and the test results were as follows: static flexural strength 108MPa, static flexural modulus 9800MPa, roller peel strength 255N·mm / mm, compression strength 9.4MPa, shear strength 2.48MPa, anti-aging and anti-oxidation effects: after 1000h anti-aging and anti-oxidation test, the first PP film 1 had no powdering and yellowing phenomenon, and the core material 5 had no powdering and yellowing phenomenon; Surface effect: The surface is smooth and flat without pits or convex spots.
[0065] Comparative Example 1:
[0066] A method for manufacturing a thermoplastic building template comprises the following manufacturing steps:
[0067] A first PP film 1, a first adhesive film 2, a skin 3, a second adhesive film 4, a core material 5, a second adhesive film 4, a skin 3, a first adhesive film 2 and a first PP film 1 are laid flat on a double steel belt continuous press in sequence and compositely pressed into a thermoplastic building formwork sample, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m 2 , vehicle speed is 3.0m / min.
[0068] The first PP film 1 is 0.2 mm thick, the PP bending strength of the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 in the skin 3 is 320 MPa, the thickness of the skin 3 is 1.0 mm, the core material 5 is a PP honeycomb core, and the density of the core material 5 is 90 kg / m 3 Anti-aging agents are added to the core material 5, the skin 3, the first PP film 1, the first adhesive film 2 and the second adhesive film 4.
[0069] The performance tests were carried out on the thermoplastic building formwork samples, and the test results were as follows: static flexural strength 62MPa, static flexural modulus 5100MPa, roller peel strength 103N·mm / mm, compression strength 2.5MPa, shear strength 0.5MPa, anti-aging and anti-oxidation effects: after 1000h anti-aging and anti-oxidation test, the first PP film 1 had no powdering and yellowing phenomenon, and the core material 5 had no powdering and yellowing phenomenon; Surface effect: The surface is smooth and flat without pits or convex spots.
[0070] Comparative Example 2:
[0071] A method for manufacturing a thermoplastic building template comprises the following manufacturing steps:
[0072] Step 1: Lay a first PP sheet film 1, a first adhesive film 2, a skin 3 and a second adhesive film 4 in sequence on a double steel belt continuous press to form a dough skin, wherein the hot plate temperature of the double steel belt continuous press is 175°C and the pressure is 10kg / m 2 , speed 0.5m / min;
[0073] Step 2: Lay the dough prepared in step 1 on the upper and lower sides of the core material 5, and put it into a double steel belt continuous press to composite and press it into a thermoplastic building formwork sample, wherein the hot plate temperature of the double steel belt continuous press is 175°C and the pressure is 10kg / m 2 , vehicle speed 0.5m / min.
[0074] The first PP film 1 is 0.2 mm, the PP bending strength in the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 in the skin 3 is 320 MPa, the thickness of the skin 3 is 1.0 mm, the core material 5 is a PP honeycomb core, and the density of the core material 5 is 300 kg / m 3 Anti-aging agents are added to the core material 5, the skin 3, the first PP film 1, the first adhesive film 2 and the second adhesive film 4.
[0075] The performance tests were carried out on the thermoplastic building formwork samples, and the test results were as follows: static flexural strength 90MPa, static flexural modulus 7950MPa, roller peel strength 130N·mm / mm, compression strength 9.6MPa, shear strength 1.3MPa, anti-aging and anti-oxidation effects: after 1000h anti-aging and anti-oxidation test, the first PP film 1 had no powdering and yellowing phenomenon, and the core material 5 had no powdering and yellowing phenomenon; Surface effect: The surface is smooth and flat without pits or convex spots.
[0076] Comparative Example 3:
[0077] A method for manufacturing a thermoplastic building template comprises the following manufacturing steps:
[0078] Step 1: Lay a first PP sheet film 1, a first adhesive film 2, a skin 3 and a second adhesive film 4 in sequence on a double steel belt continuous press to form a dough skin, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 0.4kg / m 2 , speed 0.4m / min;
[0079] Step 2: Lay the dough prepared in step 1 on the upper and lower sides of the core material 5, and put it into a double steel belt continuous press to composite and press it into a thermoplastic building formwork sample, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 0.4kg / m 2 , speed 0.4m / min;
[0080] The first PP film 1 is 0.2 mm, the PP bending strength of the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 in the skin 3 is 320 MPa, the thickness of the skin 3 is 1.0 mm, the core material 5 is a PP honeycomb core, and the density of the core material 5 is 200 kg / m 3 Anti-aging agents are added to the core material 5, the skin 3, the first PP film 1, the first adhesive film 2 and the second adhesive film 4.
[0081] The performance tests were carried out on the thermoplastic building formwork samples, and the test results were as follows: static flexural strength 80 MPa, static flexural modulus 7100 MPa, roller peel strength 120 N·mm / mm, compression strength 7.0 MPa, shear strength 1.5 MPa, anti-aging and anti-oxidation effects: after 1000h anti-aging and anti-oxidation test, the first PP film 1 had no powdering and yellowing phenomenon, and the core material 5 had no powdering and yellowing phenomenon; Surface effect: The surface is smooth and flat without pits or convex spots.
[0082] Comparative Example 4:
[0083] A method for manufacturing a thermoplastic building template comprises the following manufacturing steps:
[0084] Step 1: Lay a first PP sheet film 1, a first adhesive film 2, a skin 3 and a second adhesive film 4 in sequence on a double steel belt continuous press to form a dough skin, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m 2 , speed 3.0m / min;
[0085] Step 2: Lay the dough prepared in step 1 on the upper and lower sides of the core material 5, and put it into a double steel belt continuous press to composite and press it into a thermoplastic building formwork sample, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m 2 , speed 3.0m / min;
[0086] The first PP film 1 is 0.2 mm thick, the PP bending strength of the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 in the skin 3 is 320 MPa, the thickness of the skin 3 is 2.0 mm, the core material 5 is a PP honeycomb core, and the density of the core material 5 is 90 kg / m 3 Anti-aging agents are added to the core material 5, the skin 3, the first PP film 1, the first adhesive film 2 and the second adhesive film 4.
[0087] The performance tests were carried out on the thermoplastic building formwork samples, and the test results were as follows: static flexural strength 65MPa, static flexural modulus 5300MPa, roller peel strength 260N·mm / mm, compression strength 2.5MPa, shear strength 0.5MPa, anti-aging and anti-oxidation effects: after 1000h anti-aging and anti-oxidation test, the first PP film 1 had no powdering and yellowing phenomenon, and the core material 5 had no powdering and yellowing phenomenon; Surface effect: The surface is smooth and flat without pits or convex spots.
[0088] Comparative Example 5:
[0089] A method for manufacturing a thermoplastic building template comprises the following manufacturing steps:
[0090] Step 1: Lay a first PP sheet film 1, a first adhesive film 2, a skin 3 and a second adhesive film 4 in sequence on a double steel belt continuous press to form a dough skin, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m 2 , speed 3.0m / min;
[0091] Step 2: Lay the dough prepared in step 1 on the upper and lower sides of the core material 5, and put it into a double steel belt continuous press to composite and press it into a thermoplastic building formwork sample, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m 2 , speed 3.0m / min;
[0092] The first PP film 1 is 0.2 mm, the PP bending strength of the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 in the skin 3 is 320 MPa, the thickness of the skin 3 is 0.8 mm, the core material 5 is a PP honeycomb core, and the density of the core material 5 is 200 kg / m 3 Anti-aging agents are added to the core material 5, the skin 3, the first PP film 1, the first adhesive film 2 and the second adhesive film 4.
[0093] The performance tests were carried out on the thermoplastic building formwork samples, and the test results were as follows: static flexural strength 73MPa, static flexural modulus 5680MPa, roller peel strength 180N·mm / mm, compression strength 7.2MPa, shear strength 1.6MPa, anti-aging and anti-oxidation effects: after 1000h anti-aging and anti-oxidation test, the first PP film 1 had no powdering and yellowing phenomenon, and the core material 5 had no powdering and yellowing phenomenon; Surface effect: The surface is smooth and flat without pits or convex spots.
[0094] Comparative Example 6:
[0095] A method for manufacturing a thermoplastic building template comprises the following manufacturing steps:
[0096] Step 1: Lay a first PP sheet film 1, a first adhesive film 2, a skin 3 and a second adhesive film 4 in sequence on a double steel belt continuous press to form a dough skin, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m 2 , speed 3.0m / min;
[0097] Step 2: Lay the dough prepared in step 1 on the upper and lower sides of the core material 5, and put it into a double steel belt continuous press to composite and press it into a thermoplastic building formwork sample, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m 2 , speed 3.0m / min;
[0098] The first PP film 1 is 0.2 mm, the PP bending strength in the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 in the skin 3 is 320 MPa, the thickness of the skin 3 is 2.0 mm, the core material 5 is a PP honeycomb core, and the density of the core material 5 is 300 kg / m 3 No anti-aging agent is added to the core material 5, the skin 3, the first PP film 1, the first adhesive film 2 and the second adhesive film 4.
[0099] The performance tests were carried out on the thermoplastic building formwork samples, and the test results were as follows: static flexural strength 108MPa, static flexural modulus 10000MPa, roller peel strength 270N·mm / mm, compression strength 9.5MPa, shear strength 2.62MPa, anti-aging and anti-oxidation effects: after 1000h anti-aging and anti-oxidation test, the first PP film 1 showed powdering and yellowing, and the core material 5 showed powdering and yellowing; Surface effect: the surface is smooth and flat without pits or protrusions.
[0100] Comparative Example 7:
[0101] A method for manufacturing a thermoplastic building template comprises the following manufacturing steps:
[0102] Step 1: Lay a first PP film 1, a first adhesive film 2, a skin 3 and a second adhesive film 4 on a Teflon machine in sequence and compress them into a dough skin. The hot plate temperature of the Teflon machine is 220°C and the pressure is 5kg / m 2 , speed 3.0m / min;
[0103] Step 2: Lay the dough prepared in step 1 on the upper and lower sides of the core material 5, and put it into a Teflon machine for composite pressing to form a thermoplastic building template sample, wherein the hot plate temperature of the Teflon machine is 220°C and the pressure is 5kg / m 2 , speed 3.0m / min;
[0104] The first PP film 1 is 0.2 mm, the PP bending strength in the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 in the skin 3 is 320 MPa, the thickness of the skin 3 is 2.0 mm, the core material 5 is a PP honeycomb core, and the density of the core material 5 is 300 kg / m 3 Anti-aging agents are added to the core material 5, the skin 3, the first PP film 1, the first adhesive film 2 and the second adhesive film 4.
[0105] The performance tests were carried out on the thermoplastic building formwork samples, and the performance test results were as follows: static flexural strength 113MPa, static flexural modulus 10500MPa, roller peel strength 150N·mm / mm, compression strength 9.1MPa, shear strength 2.65MPa, anti-aging and anti-oxidation effects: after 1000h anti-aging and anti-oxidation test, the first PP film 1 had no powdering and yellowing phenomenon, and the core material 5 had no powdering and yellowing phenomenon; Surface effect: The surface was uneven, with pits and convex spots.
[0106] Comparative Example 8:
[0107] A method for manufacturing a thermoplastic building template comprises the following manufacturing steps:
[0108] Step 1: Lay a first PP film 1, a first adhesive film 2, a skin 3 and a second adhesive film 4 on a steel belt press in sequence and compress them into a dough skin. The hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m 2 , vehicle speed is 3.0m / min;
[0109] Step 2: Lay the dough prepared in step 1 on the upper and lower sides of the core material 5, and put it into a double steel belt continuous press to composite and press it into a thermoplastic building formwork sample, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m 2 , speed 3.0m / min;
[0110] The first PP film 1 is 0.2 mm, the PP bending strength of the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 in the skin 3 is 320 MPa, the thickness of the skin 3 is 2.0 mm, the core material 5 is a PET foam core, and the density of the core material 5 is 300 kg / m 3 Anti-aging agents are added to the core material 5, the skin 3, the first PP film 1, the first adhesive film 2 and the second adhesive film 4.
[0111] The performance tests were carried out on the thermoplastic building formwork samples, and the test results were as follows: static flexural strength 60MPa, static flexural modulus 5000MPa, roller peel strength 180N·mm / mm, compression strength 5.6MPa, shear strength 1.8MPa, anti-aging and anti-oxidation effects: after 1000h anti-aging and anti-oxidation test, the first PP film 1 had no powdering and yellowing phenomenon, and the core material 5 had no powdering and yellowing phenomenon; Surface effect: The surface is smooth and flat without pits or convex spots.
[0112] Comparative Example 9:
[0113] A method for manufacturing a thermoplastic building template comprises the following manufacturing steps:
[0114] Step 1: Lay a first PP sheet film 1, a first adhesive film 2, a skin 3 and a second adhesive film 4 in sequence on a double steel belt continuous press to form a dough skin, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m 2 , speed 3.0m / min;
[0115] Step 2: Lay the dough prepared in step 1 on the upper and lower sides of the core material 5, and put it into a double steel belt continuous press to composite and press it into a thermoplastic building formwork sample, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m 2 , speed 3.0m / min;
[0116] Among them, the first PP film 1 is 0.2mm, the PP bending strength in the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 in the skin 3 is 280MPa, the thickness of the skin 3 is 2.0mm, the core material 5 is a PP honeycomb core, and the density of the core material 5 is 300kg / m 3 Anti-aging agents are added to the core material 5, the skin 3, the first PP film 1, the first adhesive film 2 and the second adhesive film 4.
[0117] The performance tests were carried out on the thermoplastic building formwork samples, and the test results were as follows: static flexural strength 90MPa, static flexural modulus 8500MPa, roller peel strength 262N·mm / mm, compression strength 9.5MPa, shear strength 2.6MPa, anti-aging and anti-oxidation effects: after 1000h anti-aging and anti-oxidation test, the first PP film 1 had no powdering and yellowing phenomenon, and the core material 5 had no powdering and yellowing phenomenon; Surface effect: The surface is smooth and flat without pits or convex spots.
[0118] Comparative Example 10:
[0119] A method for manufacturing a thermoplastic building template comprises the following manufacturing steps:
[0120] Step 1: Lay a first PP sheet film 1, a first adhesive film 2, a skin 3 and a second adhesive film 4 in sequence on a double steel belt continuous press to form a dough skin, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m 2 , speed 3.0m / min;
[0121] Step 2: Lay the dough prepared in step 1 on the upper and lower sides of the core material 5, and put it into a double steel belt continuous press to composite and press it into a thermoplastic building formwork sample, wherein the hot plate temperature of the double steel belt continuous press is 220°C and the pressure is 5kg / m 2 , speed 3.0m / min;
[0122] The first PP film 1 is 0.2 mm, the PP strength of the first longitudinal unidirectional tape 32 and the second longitudinal unidirectional tape 34 in the skin 3 is 320 MPa, the skin 3 does not contain prepreg 33, the thickness of the skin 3 is 2.0 mm, the core material 5 is a PP honeycomb core, and the density of the core material 5 is 300 kg / m 3 Anti-aging agents are added to the core material 5, the skin 3, the first PP film 1, the first adhesive film 2 and the second adhesive film 4.
[0123] The performance tests were carried out on the thermoplastic building formwork samples, and the test results were as follows: static flexural strength 81 MPa, static flexural modulus 7300 MPa, roller peel strength 265 N·mm / mm, compression strength 9.38 MPa, shear strength 2.43 MPa, anti-aging and anti-oxidation effects: after 1000h anti-aging and anti-oxidation test, the first PP film 1 had no powdering and yellowing phenomenon, and the core material 5 had no powdering and yellowing phenomenon; Surface effect: The surface was uneven, with pits and convex spots.
[0124] All features described in the description, the attached claims and the drawings are essential features for the invention both individually and in any combination.
[0125] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "an implementation", "specific implementation", "other implementations", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment, implementation or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described above may also be combined in a suitable manner in any one or more embodiments, implementations or examples. The technical solutions recorded in the present invention also include technical solutions formed by any one or more of the specific features, structures, materials or characteristics described above in a separate or combined manner.
[0126] Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Ordinary technicians in the field can change, modify, replace, modify, delete some features, add features or re-combine features to form a technical solution in the above embodiments without departing from the principles and purpose of the present invention. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the innovative principles of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A thermoplastic building formwork, characterized in that: The invention comprises a core material (5), and a skin (3) and a first PP film (1) which are symmetrically arranged outward on both sides of the core material (5), wherein the first PP film (1) is bonded to the skin (3) via a first adhesive film (2), and the skin (3) is bonded to the core material (5) via a second adhesive film (4).
2. A thermoplastic building formwork according to claim 1, characterized in that: The core material (5) is a PP honeycomb core, the wall thickness of the core material (5) is 0.20-0.50 mm, the tube diameter is 5.0-15.0 mm, and the density is 100-300 kg / m 3 .
3. A thermoplastic building formwork according to claim 2, characterized in that: The skin (3) includes, from the outside to the inside, a second PP sheet film (31), a first longitudinal unidirectional tape (32), a prepreg (33) and a second longitudinal unidirectional tape (34), wherein the first longitudinal unidirectional tape (32) and the second longitudinal unidirectional tape (34) are both continuous glass fiber reinforced PP unidirectional tapes, the glass fiber content of the continuous glass fiber reinforced PP unidirectional tapes is 50% to 70%, and the first longitudinal unidirectional tape (32) and the second longitudinal unidirectional tape (34) are both 0.4-0.8 mm; the thickness of the skin (3) is 1.0-2.0 mm.
4. A thermoplastic building formwork according to claim 3, characterized in that: The prepreg (33) is a PP-based glass fiber prepreg, the PP content in the prepreg (33) is 50% to 70%, and the thickness of the prepreg (33) is 0.3-0.6 mm.
5. A thermoplastic building formwork according to claim 3, characterized in that: The bending strength of the PP in the first longitudinal unidirectional tape (32) and the second longitudinal unidirectional tape (34) is ≥300 MPa.
6. A thermoplastic building formwork according to claim 3, characterized in that: The second adhesive film (4) is a PP hot melt adhesive film, and the weight of the second adhesive film (4) is 50-200 g / m 2 , melting point is 90-180℃.
7. A thermoplastic building formwork according to claim 3, characterized in that: The first PP film (1) and the second PP film (31) both comprise a PP film and a spunlace non-woven fabric, wherein the PP film in the first PP film (1) is arranged toward a side away from the core material (5); the thickness of the first PP film (1) and the second PP film (31) are both 0.1-0.3 mm.
8. A thermoplastic building formwork according to claim 3, characterized in that: The first adhesive film (2) is a PP hot melt adhesive film, and the weight of the first adhesive film (2) is 50-200 g / m 2 , melting point is 90-180℃.
9. A thermoplastic building formwork according to claim 1, characterized in that: 0.01%-6% of anti-aging agent is added to the first PP film (1), the first adhesive film (2), the skin (3), the second adhesive film (4) and the core material (5).
10. A method for manufacturing a thermoplastic building formwork as claimed in any one of claims 1 to 9, characterized in that: The manufacturing steps include: Step 1: Lay a first PP sheet film (1), a first adhesive film (2), a skin (3) and a second adhesive film (4) in sequence on a double steel belt continuous press to form a dough skin, wherein the hot plate temperature of the double steel belt continuous press is 180-250°C and the pressure is 0.5kg / m 2 -10kg / m 2 The vehicle speed is between 0.5-5.0m / min; Step 2: Lay the dough obtained in step 1 on the upper and lower sides of the core material (5), and put it into a double steel belt continuous press to form a thermoplastic building template. The hot plate temperature of the double steel belt continuous press is 180-250°C, and the pressure is 0.5kg / m 2 -10kg / m 2 The vehicle speed is between 0.5-5.0m / min.
Citation Information
Patent Citations
Fiber-reinforced building formwork and preparation method thereof
CN105604312A